Analysis of The Effectiveness of Implementation SAP R/3 In PT. ABC - WANGKAR, Anneke (Journal of Governance, Taxation and Auditing, 2022)
This research analyses the effectiveness of SAP R/3 toward user satisfaction in using the application. The research is in PT ABC, manufactured in paper and tissue products. The research questions of this research are: "Is there any gap between the user expectation about the effectiveness of the application and the application's performance? Are some factors, which are integrated data, reliable report, processing time, and flow of information between departments significantly, affecting the user satisfaction in using SAP R/3?" The data for this research is collected using questionnaires to the employees of four departments in PT. ABC, which are the Sales and Marketing Department, Finance and Accounting Department, Production Department, and Logistics Department. The analysis used in the research is Gap Analysis and Multiple Regression Analysis. The results of this research are: "There is a gap between the user expectation about the effectiveness of the application and the application performance. There are three factors that significantly affect user satisfaction in using SAP R/3, which are integrated data, reliable report, and processing time." The benefit of the research is the effectiveness of the SAP R/3 implemented in PT. ABC. The research result can be used as a reference for further improvement of SAP R/3.The research results can be used as a reference for other companies or organizations implementing SAP R/3.